Combined high pressure and temperature induced lethal and sublethal injury of lactococcus lactis - application of multivariate statistical analysis - Kilimann, Klaus Valentin; Hartmann, Christoph; Delgado, Antonio; Vogel, Rudi; Gänzle, Michael Gerhard (International Journal of Food Microbiology, 2006)
It was the aim of this work to determine the combined effects of pressure, temperature, and co-solutes on Lactococcus lactis, and to detect correlations between culture-dependent and culture-independent methods for assessment of cellular viability and sublethal injury. Therefore, the pressure induced inactivation of L. lactis MG 1363 was investigated in buffer and in buffer with 1.5 M sucrose or 4 M NaCl at a pressure range of 0.1 to 500 MPa and a temperature range of 5 to 50 °C. The inactivation was characterised by viable cell counts, stress resistant cell counts, membrane integrity, metabolic activity, and the activity of the multi-drug-resistance transport enzyme LmrP. L. lactis was most resistant to pressure application at 20-30 °C. Sucrose protected towards inactivation at any temperature, NaCl provided protection at high temperatures only. By using Principal Component Analysis, correlations were detected between viable cell counts and metabolic activity as well as stress resistant cell counts and LmrP activity. In conclusion, the pressure-inactivation of L. lactis is strongly temperature dependent, baroprotection by sucrose occurs at any temperature but the baroprotective effects of NaCl is temperature dependent. Further on, a combination of two experimental methods fully describe lethal and sublethal injury of pressure treated cells. These simplification of data acquisition and model development facilitates the establishment of pressure processes in food technology. © 2006 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.tech.ITC.stmmec.combin
Keywords: Baroprotection; High pressure and temperature treatment; Principal component analysis